Two Siblings Showing a Mild Phenotype of Joubert Syndrome with a Specific CEP290 Variant - Uda, Daisuke; Kondo, Hidehito; Tanda, Koichi; Kizaki, Zenro; Nishida, Masashi; Dai, Hongmei; Itoh, Masayuki (Neuropediatrics, 2022)
Joubert syndrome (JS) is a genetic neurodevelopmental disorder characterized by lower brainstem dysplasia and cerebellar vermis agenesis termed molar tooth sign (MTS), psychomotor retardation, abnormal respiratory pattern in infancy, and oculomotor abnormalities. Arima syndrome (AS), which is a severe form of JS, is characterized by severe psychomotor retardation, congenital visual impairment, progressive renal dysfunction, and lower brainstem dysplasia from early infancy. Numerous patients with AS expire in early childhood. Recently, c.6012–12T> A in the CEP290 gene was reported as a specific variant of AS. Herein, we report the cases of two siblings showing a phenotype of JS with compound heterozygous mutations (c.6012–12T > A / c.5924delT) in the CEP290 gene. The older sister (aged 19 years) had hypotonia, hypertelorism, and anteverted nares since birth. As a neonate, she developed a transient abnormal respiratory pattern and nystagmus, and brain magnetic resonance imaging (MRI) showed MTS. The younger sister (aged 13 years) exhibited mild hypotonia and pendular nystagmus as a neonate; MRI revealed MTS. Both sisters had psychomotor retardation, oculomotor dysfunction, and bilateral renal cysts with normal renal function. They can walk and have simple conversation. They do not meet the diagnostic criteria for AS, and their symptoms were milder than those of previously reported cases with this specific mutation. This report indicates the expanding spectrum of the CEP290 variant.
Keywords: Joubert syndrome; CEP290; Arima syndrome